Geomechanics and Geotechnics of Particulate Media : proceedings of the International Symposium on Geomechanics and Geotechnics of Particulate Media, Ube, Yamaguchi, Japan, 12-14 September 2006 /: proceedings of the International Symposium on Geomechanics and Geotechnics of Particulate Media, Ube, Yamaguchi, Japan, 12-14 September 2006. ([2017?]) - Unknown
No abstract available